Utility and economical value of treated paddy straw fed to the lactating buffaloes (Indian Journal of Animal Production and Management, 2017)
A field level study was conducted to investigate the prospective of treated paddy straw feeding to the lactating  buffaloes belonging to small and large category farmers. Twenty four lactating buffaloes were selected in  each category among which 12 buffaloes were fed with urea treated paddy straw and 12 were fed with  untreated straw in their mixed ration. The paddy straw was treated with 65 litter of water as 6 percent urea  solution/100 kg straw mixed with berseem and local available concentrate fed to lactating buffaloes. It was  found that the urea treatment cost of small farmers was more than large farmer. During the study found  that milk yield in lactating animals fed with urea treated straw were 5.92 liters for small farmers (T1) and  6.30 liters for large farmers (T2) which was higher compared to the animals fed with untreated straw (5.37  and 5.85 liters , respectively for small and large farmers. The overall income over the feed cost/animal/ day was higher for farmers following urea treatment than farmers who practiced traditional feeding. It may  conclude that urea treatment technique improved the quality of paddy straw with respect to its utilization  and economic value in lactating buffalo. Therefore study indicated picture that large farmers can take more  profit if they opted the technique for improve the nutritive value of paddy straw.
Keywords: Buffalo; Lactating buffaloes; Practical utility; Urea Treatment